Innovation in Sustainable Consumption: Exploring the Popularity of Thrifting among College Students in Indonesia - Grace Monika Mei Corebima; Nuraini Indah Rahmawati; Yuni Prianingsih Longa; Anysia Magdalis Saunoah; Andreas Sandika Dhone Sina; Enike Tje Yustin Dima (Yayasan Pendidikan Islam Al-Matani, 2026)
The growing popularity of thrifting among college students reflects a significant shift in consumer behavior toward more sustainable and innovative consumption practices. Once associated primarily with financial limitations, thrifting has evolved into a lifestyle that combines affordability, self-expression, environmental awareness, and digital engagement. This study aims to explore college students' perspectives on the thrifting phenomenon, identify the factors driving its increasing popularity, examine the main motivations underlying thrift shopping, and analyze the perceived quality and implications of using second-hand clothing. A qualitative descriptive approach was employed through a systematic literature review of scholarly articles, books, industry reports, and credible online sources related to sustainable fashion, circular economy, and consumer behavior. The collected data were analyzed using qualitative content analysis involving data reduction, thematic categorization, and interpretation. The findings reveal that students perceive thrifting as an innovative form of sustainable consumption that enables smart financial management, promotes individuality through unique fashion choices, and supports environmental sustainability by extending the lifecycle of clothing. The rapid growth of digital platforms, social media marketing, and access to affordable branded and vintage products further accelerate the adoption of thrifting among young consumers. Although concerns regarding hygiene and product safety remain, these challenges can be minimized through appropriate cleaning and sterilization practices. This study concludes that thrifting represents more than an economical shopping alternative; it is an innovation in sustainable consumption that integrates economic value, social identity, environmental responsibility, and digital culture. The findings contribute to the growing literature on sustainable fashion and provide practical insights for policymakers, educational institutions, and fashion industry stakeholders in promoting responsible consumption among younger generations.